2009
DOI: 10.1302/0301-620x.91b7.21476
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and accuracy of digital templating in total knee replacement

Abstract: We aimed to determine the reliability, accuracy and the clinical role of digital templating in the pre-operative work-up for total knee replacement. Initially a sample of ten pre-operative digital radiographs were templated by four independent observers to determine the inter- and intra-observer reliability of the process. Digital templating was then performed on the radiographs of 40 consecutive patients undergoing total knee replacement by a consultant surgeon not involved with the operation, who was blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 11 publications
7
44
0
Order By: Relevance
“…Directly compared to planning of the femoral component, templating of the tibial component was more accurate. Trickett et al reported similar results [24] whereas Miller et al reported a more accurate size planning for the femoral component [25].…”
Section: Discussionmentioning
confidence: 94%
“…Directly compared to planning of the femoral component, templating of the tibial component was more accurate. Trickett et al reported similar results [24] whereas Miller et al reported a more accurate size planning for the femoral component [25].…”
Section: Discussionmentioning
confidence: 94%
“…In their study, they found the template of the femoral component was accurate 48% of the time and within 1 size 98% of the time. When they evaluated the tibia component, the template was accurate 55% of the time and within 1 size in 100% of their patients 6 . Specht et al evaluated accuracy of templating when comparing digital to acetate templating in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown mixed results for templating in knee and hip arthroplasty, although little information is known about its use for the shoulder. [26][27][28][29] There has been one study regarding the reliability and accuracy of pre-operative analogue templates in shoulder arthroplasty; however, no studies have been published using digital templating or evaluating the use of templating for humeral neck angle. 11 The present study measured the reliability and accuracy of pre-operative digital templating for predicting head size, stem size and neck angle in shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%